Novel, Green, and Scalable Aqueous Synthesis of Yellow–Green Emitting Cs3Cu2Cl5 Scintillator and its Application in High‐Resolution TFT Panel for X‐Ray Imaging Detector. Issue 3 (1st December 2022) - Wang, Zhicheng; Guo, Jiale; Lin, Qi‐Sheng; Rao, Guanghui; Zhao, Jingtai; Yang, Chengzhang; He, Weixiang; Wang, Chujie; Zhang, Zhijun
Abstract: Copper‐based metal halide scintillators have received increasing attention due to their high light yield and nontoxicity. However, the synthetic methods are still not feasible for actual commercialization for the difficulty in scaling up and the absence of green chemical footprint. Herein,  we report a new, simple, aqueous synthetic method for the mass production of highly purified and crystallized Cs3 Cu2 Cl5 powder by a room‐temperature reaction between a saturated aqueous solution of CsCl and a saturated hydrochloric acid solution of CuCl. The product exhibits a photoluminence peak centering at 527 nm (FWHM = 106.7 nm) and a quantum yield (PLQY) of 97%. A prototype X‐ray imaging detector is fabricated by coupling a large area scintillation screen prepared by blade coating of Cs3 Cu2 Cl5 powder and a commercial thin‐film transistor (TFT) panel (16 cm × 13 cm, 125 µm pixel size) with readout circuit. The device exhibits a high spatial resolution of 4 lp mm −1, exceeding the theoretical limit of the TFT panel, and an excellent dynamic imaging ability. In short, this work demonstrates an efficient novel synthetic method of Cs3 Cu2 Cl5 and its application as X‐ray imaging device, providing an applicable solution for its future commercialization. Abstract : An aqueous phase synthesis method is proposed which can easily scale up and mass produce Cs3 Cu2 Cl5 . The Cs3 Cu2 Cl5 film combined with a 125 µm pixel size thin‐film transistor (TFT) panel proves for the first time that the combination of copper‐based halides and X‐ray imaging detector has good static and dynamic imaging ability, and the resolution reaches the design upper limit of 4 lp mm −1 .